Engineering bacteriophage for a pragmatic low-resource setting bacterial diagnostic platform. Issue 3 (1st April 2016) - Talbert, Joey N.; Alcaine, Samuel D.; Nugen, Sam R.
ABSTRACT: Bacteriophages represent multifaceted building blocks that can be incorporated as substitutes for, or in unison with other detection methods, to create powerful new diagnostics for the detection of bacteria. The ease of phage manipulation, production, and detection speed clearly highlights that there remains unrealized opportunities to leverage these phage-based components in diagnostics amenable to resource-limited settings. The passage of regulations like the Food Safety Modernization act, and the ever increasing extent of global trade and travel, will create further demand for these types of diagnostics. While phage-based diagnostics have begun to entering the market place, further research is needed to ensure the potential benefits of phage-based technologies for public health are fully realized. We are just beginning to explore the possibilities that phage-based detection can offer us in the future. The combination of engineered phages as well as engineered enzymes could result in ultrasensitive detection systems for low-resource settings. Because the reporter enzyme is synthesized in vivo, we need to consider the options outside of normal enzyme reporters. In this case, common enzyme issues such as purification and long-term stability are less important. Phage-based diagnostics were conceptualized from out-of-the box thinking and the evolution of these systems should be as well.